Narrative and Argumentation in a Case of Alleged Child Abuse - Baldwin, Clive; Greason, Michelle (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2019)
The relationship between argument and narrative has been the subject of much debate, particularly in the area of law, where a number of theorists have argued for the priority of one over the other in the decision-making process, the premise being that argumentation and narrative are two distinct text forms. Through the rhetorical analysis of a series of expert reports in a case of alleged child abuse, we seek to explore the dynamics between argumentation and narrative. In so doing, we argue that while certain actions may undermine the robustness of an argument, it is these very actions that make possible the telling of a persuasive story. We conclude with a plea for the development of rhetorical skills among social workers so as to be better able to discern future directions for the benefit of service users.